Hubungan Pengetahuan Kesehatan Reproduksi Remaja Dengan Sikap Seksual Pranikah Di Desa Bangun Rejo Kecamatan Tanjung Morawa Tahun 2023 - Ika Damayanti Sipayung; Ridesman Ridesman; Marta Armita Silaban; Damayanty S; Hadisyah Hadisyah (An-Najat, 2023)
The number of unwanted pregnancies has been experienced by many young women and married women due to premarital sexual activity. Negative premarital sexual attitudes can cause unwanted pregnancies in adolescents which can cause reproductive health problems which can lead to an increase in maternal mortality in Indonesia due to the desire for abortion. One factor in negative sexual attitudes is limited knowledge in adolescent reproductive health. The aim of this study was to determine the relationship between knowledge of adolescent reproductive health and premarital sexual attitudes in Bangun Rejo Village, Tanjung Morawa District in 2023. The research method was an analytical survey, this type of research used observational with a cross sectional approach, sampling used purposive sampling. Subjects in the case were 80 adolescents who had met the inclusion and exclusion criteria. Data were collected using a questionnaire and distributed to respondents, analyzed using univariate and bivariate an alysis using chi square analysis. The results of the study showed that there was a significant relationship between knowledge of adolescent reproductive health and premarital sexual attitudes, p-value 0.000 (α = 0.05). From this study it can be concluded that there is a significant relationship between knowledge of adolescent reproductive health and sexual attitudes of premarital adolescents